Cloud-Based Learning to Improve Student’s Participation Ability in Higher Education - Deswidya Hutauruk; sanjaya pinem; Elsida Aritonang (Sean Institute, 2023)
One notable benefit associated with utilizing internet-based media for learning purposes is its inherent accessibility from any location. Despite the presence of forgiveness, face-to-face learning is not without its limitations, albeit they cannot be entirely eradicated. The objective of this research is to strengthen students' capacity to engage and actively participate in cloud-based learning, hence fostering improved student engagement. Class Action Research is used in this study in two stages. The Class Action Research framework encompasses four key components: planning, implementation, observation, and reflection. The findings for this study indicate that there is potential for enhancing the utilization of cloud-based learning. This phenomenon is seen in the heightened level of student engagement prior to the initial academic period, with 13.33% displaying active participation, 17.78% demonstrating discipline, and a mere 10% exhibiting attentiveness towards the learning process. The consecutive outcomes following the second iteration were 64.44%, 71.11%, and 67.78%. Therefore, it can be concluded that the utilization of cloud-based learning enhances the capacity to deliver higher students’ participant.